Post Preloading Creep Properties of Highly Compressible Harbor Marine Sediments - Toha, Franciscus Xaverius (Journal of Engineering and Technological Sciences, 2017)
A laboratory experimental research in creep behavior of soft clay marine sediments was done to investigate creep strain under reloading. A total of 52 oedometer tests were carried out with 16 slurry sediment samples subjected to cycles of unloading at preload removal pressure and reloading to higher design pressures. Common practice as well as more recent advanced methods of creep deformation analysis were used to refine the predictions. The study indicates that although preloading substantially reduces post construction creep, the analysis is very sensitive to creep indices at slight overconsolidation and the resulting creep may not be negligible at previously established limits of primary to secondary compression ratios.